The Influence of Length of Stay on Traveler Purchase Decisions for Franchise Fast Food Establishments in South Korea. (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Food plays a significant role in cultural expression and daily life creativity across various cultures. This study aims to investigate the impact of fast-food restaurants on food travelers in Korea, focusing on the evolving preferences of travelers and the role of franchise establishments in meeting those preferences. As food tourism gains popularity in Korea, travelers' perception of food influences their behavior, emphasizing the importance of understanding a destination's culinary reputation. The study delves into the preferences and decision-making process related to fast-food restaurants using the SIT. The study explores how the duration of a traveler's stay influences their purchasing decisions, specifically analyzing the purchasing behavior of travelers regarding different franchise fast food restaurants during their time in Korea.